The Effect of Transformational Leadership Style, Communication, and Competence on Service Quality with Organizational Commitment as an Intervening Variable - Vina Amalia; Faris Faruqi (Jurnal Riset Manajemen dan Bisnis, 2024)
This study aims to analyze the effect of transformational leadership style, communication, and competence on service quality with organizational commitment as an intervening variable at PT RB Group. This study uses a quantitative approach research method with multiple linear regression analysis data analysis techniques using Structural Equation Modeling (SEM) Jamovi 2.6.19 software. The population of this study were all employees and management who worked at PT RB. Group. purposive sampling method, with a total sample size of 4 PT RB Group companies so that the total in this study was 201 samples. The data used in this study is a survey method using a questionnaire as a data collection tool. Based on the results of the study, it shows that transformational leadership style, communication, and competence have a positive and significant effect on service quality. organizational commitment is proven to mediate the relationship between independent variables and service quality. this indicates that increasing transformational leadership, effective communication, and developing employee competence can improve the quality of service provided by the company.